2016
DOI: 10.1021/acssuschemeng.6b00091
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Deep Eutectic Solvents in Extraction of Bioactive Natural Products

Abstract: Deep eutectic solvents (DESs) are emerging as green and sustainable solvents for efficient extraction of bioactive compounds or drugs. This work aimed to comprehensively evaluate the potential and effectiveness of DESs for extraction of different types of natural compounds from biomass. Five Chinese herbal medicines including Berberidis Radix, Epimedii Folium, Notoginseng Radix et Rhizoma, Rhei Rhizoma et Radix, and Salviae Miltiorrhizae Radix et Rhizoma were selected to assess the efficiency of DESs on extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
251
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(284 citation statements)
references
References 30 publications
(34 reference statements)
12
251
1
2
Order By: Relevance
“…According to the data available in the literature, viscosities and/or densities for the investigated DESs are as follows: ChCl : fructose [12]. Addition of 25% and 50% of water significantly improved rutin extraction in all experiments, which could be attributed to the decrease in the viscosity of the DESs by addition of water, as described by Duan et al [6] and Zhao et al [11]. When rutin extraction yields are compared, there is no significant difference among the experiments performed with addition of 50% and 25% of water with the same DES, and, as indicated in Figure 1, there is no need to perform the extraction for 3 or 6 h.…”
Section: Selection Of the Best Des For Rutin Extractionsupporting
confidence: 52%
See 1 more Smart Citation
“…According to the data available in the literature, viscosities and/or densities for the investigated DESs are as follows: ChCl : fructose [12]. Addition of 25% and 50% of water significantly improved rutin extraction in all experiments, which could be attributed to the decrease in the viscosity of the DESs by addition of water, as described by Duan et al [6] and Zhao et al [11]. When rutin extraction yields are compared, there is no significant difference among the experiments performed with addition of 50% and 25% of water with the same DES, and, as indicated in Figure 1, there is no need to perform the extraction for 3 or 6 h.…”
Section: Selection Of the Best Des For Rutin Extractionsupporting
confidence: 52%
“…Data in Figure 1 indicate that pure DES without addition of water has the lowest ability to extract rutin at all extraction times. This is a reasonable result since the viscosity and density of the applied DESs are high, thus causing slow mass transfer [6]. According to the data available in the literature, viscosities and/or densities for the investigated DESs are as follows: ChCl : fructose [12].…”
Section: Selection Of the Best Des For Rutin Extractionmentioning
confidence: 78%
“…To our knowledge, no published data are available related to the in vivo effects of NADES as administration tools for bioactive constituents. These eutectics, prepared using different starting materials, can be divided into five groups, the first is based on urea (1-4), the second on polyalcohols and sugars (5-6), the third on organic acid and sugars (7)(8)(9), the fourth on organic acid and amino acid (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and the fifth group was prepared using choline chloride, sugars and amino acid (28)(29)(30). Our results show the ability of various NADES to dissolve rutin.…”
Section: Rutin Solubility In the Different Prepared Nadesmentioning
confidence: 99%
“…In an attempt to broaden the usage of DESs in the extraction of bioactive compounds from plants, Duan et al, [44] have used many choline chloride, betaine (Bet)-, and L-proline (Pro)-based DESs to extract alkaloids, phenolic acids, saponins, flavonoids and anthraquinones from five Chinese herbal medicines (Berberidis Radix, Epimedii Folium, Notoginseng Radix et Rhizoma, Rhei Rhizoma et Radix, and Salviae Miltiorrhizae Radix et Rhizoma).Their findings showed that most of the DESs used were more effective in extracting alkaloids than anthraquinones. The researchers concluded that the extraction ability of DES may be associated with their physicochemical properties, including hydrogen bonding interactions, polarity, viscosity, and pH.…”
Section: Deep Eutectic Solvent As a Novel Benign Extractant For Bioacmentioning
confidence: 99%